A review of microwave-assisted advanced oxidation processes for wastewater treatment. (January 2022) - Xia, Huiling; Li, Chengwei; Yang, Guoying; Shi, Zhiang; Jin, Chenxi; He, Wenzhi; Xu, Jingcheng; Li, Guangming
Abstract: Microwave (MW) technology has gained increasing interest in wastewater treatment due to its unique properties, such as fast and uniform heating, hot spots effect, and non-thermal effect. MW enhances the production of active radicals (e.g., OH, SO4 − ), which exerts a stronger integrated treatment effect in combination with advanced oxidation processes. Over the years, microwave-assisted advanced oxidation processes (MW-AOPs) have developed rapidly to degrade pollutants as innovative treatment approaches. This paper provides a detailed classification and a comprehensive review of MW-AOPs. The latest applications of MW in different advanced oxidation systems (oxidation systems, catalytic oxidation systems, and photochemical, electrochemical and sonochemical systems) are reviewed. The reaction parameters and performance of MW-AOPs in wastewater treatment are discussed, and the enhancement of pollutant degradation by MW is highlighted. In addition, the operating costs of MW-AOPs are evaluated. Some recommendations on MW-AOPs are made for future research. This review provides meaningful information on the potential development and evolution of MW-AOPs. Graphical abstract: Image 1 Highlights: The mechanisms of MW in various AOPs are summarized. Three types of MW-AOPs based on different oxidation systems are described. The synergistic effect in the MW catalytic oxidation system is discussed. The advantages of MW-assisted photochemical, electrochemical, and sonochemical AOPs are demonstrated. The economic costs of MW-AOPs are evaluated.